2021
DOI: 10.1002/hep4.1656
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Enhancer Factor Domain Family member 4 Exerts an Oncogenic Role in Hepatocellular Carcinoma by Hippo‐Independent Regulation of Heat Shock Protein 70 Family Members

Abstract: Transcriptional enhancer factor domain family member 4 (TEAD4) is a downstream effector of the conserved Hippo signaling pathway, regulating the expression of genes involved in cell proliferation and differentiation. It is up‐regulated in several cancer types and is associated with metastasis and poor prognosis. However, its role in hepatocellular carcinoma (HCC) remains largely unexplored. Using data from The Cancer Genome Atlas, we found that TEAD4 was overexpressed in HCC and was associated with aggressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…TEAD4 is a key member of the TEAD family and it binds to different cofactors to regulate the transcription of target genes that involved in cellular cell functions [22]. TEAD4 plays an oncogenic role in many cancers including gastric cancer, hepatocellular carcinoma, lung adenocarcinoma and head neck squamous cell carcinoma by increasing cancer cell proliferation, migration and epithelial-mesenchymal transition (EMT) [46][47][48]. For example, Li et al reported that YAP/TEAD4 interaction mediates transcriptional activity of KIF4A promoter by binding KIF4A promoter, which will promote cell growth of esophageal squamous cell carcinoma (ESCC) cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…TEAD4 is a key member of the TEAD family and it binds to different cofactors to regulate the transcription of target genes that involved in cellular cell functions [22]. TEAD4 plays an oncogenic role in many cancers including gastric cancer, hepatocellular carcinoma, lung adenocarcinoma and head neck squamous cell carcinoma by increasing cancer cell proliferation, migration and epithelial-mesenchymal transition (EMT) [46][47][48]. For example, Li et al reported that YAP/TEAD4 interaction mediates transcriptional activity of KIF4A promoter by binding KIF4A promoter, which will promote cell growth of esophageal squamous cell carcinoma (ESCC) cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…NR2F2 and OSM have been shown to be related to metastasis in gastric cancer and breast cancer, respectively (33,34); HSPA6 has been shown to play a critical role in the recurrence of hepatocellular carcinoma (35); AR has been shown to play a crucial role in cancer progression and continues to be a primary therapeutic target in prostate cancer (36). However, these previous studies (33)(34)(35)(36) included limited direct information about the IRGs of primary ESCA. Thus, these genes' immunomodulatory roles in monitoring the progression of primary ESCA and predicting prognosis need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed as previously described ( 22 , 23 ). Briefly, 8 μm-thick sections were cut, dehydrated, and processed on a Bond III (Leica Biosystems Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%